Clinical significance of ST depression at exercise stress testing in competitive athletes: usefulness of coronary CT during screening - Sperandii, F.; Guerra, E.; Tranchita, E.; Minganti, C.; Lanzillo, C.; Nigro, A.; Quaranta, F.; Parisi, A.; Di Roma, M.; Maresca, L.; Fagnani, F.; Calo, L. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Congenital coronary anomalies (CCAs) and coronary artery disease (CAD) arouse intense scientific and clinical interest in sports medicine and sports cardiology medical communities because of their potential to trigger sudden cardiac death (SCD) in athletes. Exercise stress testing represent the first instrumental assessment to evaluate electrocardiographic changes during effort. Coronary computed tomography angiography (CCTA) is an advanced accurate noninvasive imaging modality for excluding CAD and abnormalities of origin and course of coronary vessels. The aim of this study is to investigate with CCTA the clinical significance of ST depression suggestive for myocardial ischemia during exercise stress testing in athletes and to determine the prevalence of CAD and/or CCAs. METHODS: Sixty-five consecutive athletes showing electrocardiographic findings positive or equivocal for myocardial ischemia on exercise stress testing during pre-participation screening were investigated with CCTA. RESULTS: Among the 65 athletes investigated, 36 showed Myocardial Bridge (MB), one showed an anomalous coronary origin and seven showed CAD. Among 36 athletes with MB, 4 were associated with mild coronary artery stenosis. Three athletes with CAD needed percutaneous transluminal coronary angioplasty or coronary artery bypass surgery. CONCLUSIONS: In competitive athletes even with excellent workload capacities, in absence of cardiomyopathy, the presence of ischemic electrocardiographic abnormalities could be mainly determined by a coronary congenital or acquired pathology. In this population CCTA is a useful imaging modality of choice for the risk stratification and for the diagnostic process, to allow eligible athletes to compete and to follow-up subjects requiring medical surveillance.